UiTM Tapah non-resident rental housing application / Nurul Afiqah Ayob ...[et al.] - Nurul Afiqah, Ayob; Nur Hasni, Nasrudin; Samsiah, Ahmad; Rosida, Ahmad Junid (UiTM Press, 2020)
Student accommodation is a vital issue in building a student's life at any university. Students and universities struggle to find the right solution for housing so that students can pursue their particular field of study and enjoy their university's life. Seemingly, the right accommodation can contribute towards students' success, students' retention rate, and students' satisfaction with their living arrangement. As it turns out, the Non-Resident students of University Teknologi MARA Perak, Tapah Branch voiced out their unhappiness to the University's Management that they are having difficulties in finding rental housing around the Tapah area. The researches believed that the students complained need to be addressed immediately. Considerately, a mobile application was developed to help them in finding off-campus rental housing around the Tapah area. Usability testing has been applied to evaluate the feedback of users regarding their satisfaction using this new mobile application. The result from the survey shows 94.4 % of the users were satisfied with the overall system. However, there are still some future works that need to be done to improve this application.